Microbubble contrast-enhanced ultrasound in the vascular evaluation after pancreas transplantation: a single-center experience. (October 2019) - Berstad, Audun E; Brabrand, Knut; Horneland, Rune; Syversveen, Trygve; Haugaa, Håkon; Jenssen, Trond G; Foss, Aksel
Background: Arterial and venous thrombosis are feared complications of pancreas transplantation (PTx). Microbubble contrast-enhanced ultrasound (CEUS) is a non-invasive imaging technique that can augment diagnostic capabilities of transplant organ perfusion. Purpose: To document the state to which CEUS can improve the vascular evaluation of PTx compared to conventional Doppler ultrasound (US) directly after surgery. Material and Methods: A total of 129 consecutive PTx in 128 adult patients were eligible for inclusion. The duodenal segment of the graft was anastomosed to the native duodenum. Within 12 h postoperatively, graft circulation was monitored by Doppler US in 116 PTx performed in 116 patients (69 men, 47 women; mean age =41 years). CEUS was performed with a sulfur hexafluoride-containing contrast agent (SonoVue) intravenously if the examiner was not able to confirm normal graft circulation. Image quality was documented by two independent observers on a 4-point scale: 1 = excellent; 2 = minor diagnostic limitations; 3 = major diagnostic limitations; and 4 = non-diagnostic. Results: In the early postoperative phase, 79 (68%) of 116 PTx were examined with Doppler US only. Of these, 52 were of excellent quality (grade 1), 22 of good quality (grade 2), and five were of grade 3 or 4 quality. Thirty-seven (32%) examinations were supplemented by CEUS. CEUS significantly improved examination quality compared to Doppler US alone (median visualization score 1.5 vs. 2.5, respectively; P  < 0.0001). Conclusion: CEUS can significantly improve vascular evaluation of PTx compared to Doppler US alone in the early postoperative phase.